Association Between Previous or Active Cancer and Clinical Outcomes in TAVR Patients: A Systematic Review and Meta-Analysis of 255,840 Patients - Diaz-Arocutipa, Carlos; Torres-Valencia, Javier; Zavaleta-Camacho, Gabriela; Vicent, Lourdes (Frontiers in Cardiovascular Medicine, 2021)
Background: It has been proposed that transcatheter aortic valve replacement (TAVR) may be an option for patients with cancer and severe aortic stenosis. We assessed the association between previous or active cancer and clinical outcomes in TAVR patients. Methods: We searched four electronic databases from inception to March 05, 2021. The primary outcome was all-cause mortality. Secondary outcomes were cardiovascular mortality, myocardial infarction, stroke, acute kidney injury, pacemaker implantation, major bleeding, and vascular complications. All meta-analyses were performed using a random-effects model. Relative risks (RRs) and adjusted hazard ratios (aHRs) with their 95% confidence interval (95% CI) were pooled. Results: Thirteen cohort studies involving 255,840 patients were included. The time period for mortality ranged from inpatient to 10 years. Patients with active cancer had a higher risk of all-cause mortality using both crude (RR, 1.46; 95% CI, 1.13-1.88) and adjusted (aHR, 1.79; 95% CI, 1.43-2.25) estimates compared to non-cancer group. In contrast, the risk of cardiovascular mortality (RR, 1.26; 95% CI, 0.58-2.73), myocardial infarction (RR, 0.94; 95% CI, 0.34-2.57), stroke (RR, 0.90; 95% CI, 0.75-1.09), pacemaker implantation (RR, 0.87; 95% CI, 0.50-1.53), acute kidney injury (RR, 0.88; 95% CI, 0.74-1.04), major bleeding (RR, 1.15; 95% CI, 0.80-1.66), and vascular complications (RR, 0.96; 95% CI, 0.79-1.18) was similar between patients with or without cancer. Conclusion: Our review shows that TAVR patients with active cancer had an increased risk of all-cause mortality. No significant association with secondary outcomes was found.